Dehydration in New Zealand fishing vessel crews. (August 2019) - Edwin, Marion; Moore, Dave; Guard, Darren
Highlights: This exploratory research identifies that high levels of dehydration are common for New Zealand fishers. This presents a health and safety risk whilst they are working, along with the potential for long term health problems. Abstract: An exploratory investigation of hydration levels of fishers aboard three working fishing vessels in New Zealand waters identified that crew hypo-hydration was common. The opportunity to collect this data occurred in the context of ergonomics work to discover opportunities to reduce musculoskeletal injury rates for fishers. Hydration was considered worthy of inclusion in this exploratory work following anecdotal suggestion that urinary tract and kidney infections were perhaps common in crew. Whilst dehydration-related health problems and detrimental effects on worker performance are well understood, the international literature revealed no previous hydration evaluation specific to fishing crews. Dehydration research has however been reported from forestry, mining and manual labour industries with knowledge that can be applied to the maritime work environment. Hydration (urine specific gravity) was measured with a manual refractometer from crew volunteering to participate, and findings shared with participants. On-vessel crew education regarding hydration practices and factors that may contribute to improved hydration allowed some crew to improve their hydration status, whilst others became more dehydrated during the five week trip. The hypo-hydration finding is concerning as trawler crew work rotating shifts for 7 days per week for periods of up to 6 weeks at sea with potential for dehydration-related health and safety impacts, and productivity loss.